Construcción de noticias políticas en un diario especializado en economía. El caso Lava Jato en el diario Gestión - Arcasi Mariño, Walter Gonzalo (2021)
This work of professional sufficiency describes and analyzes the process of construction of political news in the newspaper Gestión, the only newspaper specialized in economics in Perú, developed by the bachelor at the juncture of the Lava Jato case. In addition, it documents an experience already completed between 2015 and 2019 in the aforementioned media, in which the editor works to date. With it, it seeks to explain the particularities of an agenda that articulates two thematic fields (the political and the economic) to produce information. This analysis will make it possible to identify the use of specialized sources, the collection of information, the commissioning of the commission, the elaboration of the headline, the focus of the story and the limitations of the journalist.